Keefektifan Model Pembelajaran Discovery Learning Terhadap Hasil Belajar Peserta Didik Kelas X MAN Bantaeng - Fauzia Yunsyahana; Army Auliah; Muhammad Jasri Djangi (Universitas Negeri Medan, 2022)
This pre-experimental study aims to determine the effectiveness of the online Discovery Learning Model the Learning Outcomes of Students in Class at MAN Bantaeng on Oxidation Reduction Main Reaction Material. The research design used is a one-shot case study. The sample in this study were all the students in class X MIA 1 MAN which consisted of 22 students. Data was collected by presenting a post-test to the experimental class. This study uses descriptive and inferential statistical analysis. The results showed that the average value of the learning outcomes was 82.8, the percentage of class completeness was 86.3%, the percentage of completeness indicators was 83.90%, the average of the student response was 75.5%, and the percentage of student activity was 73%. In testing the hypothesis using the Wilcoxon signed rank test with = 0.05, the probability < (0.001 < 0.05). With this, it can be concluded that the application of the Discovery Learning model improves the students’ learning outcomes of class X MIA 1 MAN Bantaeng on the reduction reaction material subject matter.Keywords: Effectiveness, Discovery Learning, reduction oxidation reaction